Product development management: integrating the lean approach during conceptual design - Dal Forno, Ana Julia; B. Barquet, Ana Paula; Buson, Marcos A.; Gitirana G. Ferreira, Marcelo (Revista Gestão da Produção Operações e Sistemas, 2008)
With the trend in reducing the life cycle of products, new ideas are demanded by an increasingly volatile and demanding market. Turning these ideas into sustainable projects, which meets the needs and expectations of consumers throughout the business process, has a direct impact on the survival of a corporation. With the dissemination of Lean principles, which seeks an increase in value and waste reduction, opportunities to improve performance were identified in production systems. Since then, the search itself aims at guiding the process identifying value by their stakeholders and adapting it according to company culture. These same principles are being applied to Product Process Development (PPD) at companies. The objective of this paper is to show how to use these principles in the early stages of PPD, specifically the Concept Project phase, in developing an electronic product. Thus, through a case study, aspects are raised such as lead time reduction, flexibility to change, and the implementation of Set-based Concurrent Engineering (SBCE) to select the best product design. This case shows the influence of lean principles in waste reduction and adding value during PPD. Key-words: Lean; Set-based Concurrent Engineering.